Uji ResistensiStaphylococcus aureusTerhadap Antibiotik, Amoxillin, Tetracyclin dan Propolis - Mardiah Mardiah (Universitas Hasanuddin, 2017)
This research was motivated by the presence of Staphylococcus aureus which is one of the main causes of the high infection so that treatment is not adequate to produce a new problem that resistance to the drugs. The purpose of this study is to determine and compare the resistance of Staphylococcus aureus to antibiotics amoxicillin, tetracycline and propolis. This type of research is quantitative experiments where samples used are germ control with treatment 3 times. Based on the results of research which is conducted, showed that the antibiotics amoxicillin and propolis is an antibiotic which can inhibit the growth of Staphylococcus aureus which antibiotics amoxicillin with a diameter of inhibition zone average of 14 mm and propolis with an average inhibition zone of 15.1 mm, while the antibiotic tetracycline-resistant Staphylococcus aureus to obtain inhibition zone 0 mm. For further research is no longer using the method of control germs but using a sample directly from infected patients and for the relevant institutions would be able to provide materials that will be used for research, especially pencadang.